Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To factor the expression \(27m^3 + 64n^3\), we need to recognize that it is a sum of cubes. The sum of cubes can be factored using the following general formula:
[tex]\[a^3 + b^3 = (a + b)(a^2 - ab + b^2)\][/tex]
In our case, the expression \(27m^3 + 64n^3\) can be written in terms of cubes:
[tex]\[27m^3 = (3m)^3\][/tex]
[tex]\[64n^3 = (4n)^3\][/tex]
So, we can rewrite the expression like this:
[tex]\[(3m)^3 + (4n)^3\][/tex]
Now, we can apply the sum of cubes formula with \(a = 3m\) and \(b = 4n\):
[tex]\[(3m)^3 + (4n)^3 = (3m + 4n)((3m)^2 - (3m)(4n) + (4n)^2)\][/tex]
We need to perform the operations inside the parentheses to get the final factors:
1. \((3m)^2 = 9m^2\)
2. \((3m)(4n) = 12mn\)
3. \((4n)^2 = 16n^2\)
Putting these together, we have:
[tex]\[(3m)^3 + (4n)^3 = (3m + 4n)(9m^2 - 12mn + 16n^2)\][/tex]
So, the factored form of the expression \(27m^3 + 64n^3\) is:
[tex]\[(3m + 4n)(9m^2 - 12mn + 16n^2)\][/tex]
Therefore, the factors of \(27m^3 + 64n^3\) are:
[tex]\[ (3m + 4n) \quad \text{and} \quad (9m^2 - 12mn + 16n^2) \][/tex]
[tex]\[a^3 + b^3 = (a + b)(a^2 - ab + b^2)\][/tex]
In our case, the expression \(27m^3 + 64n^3\) can be written in terms of cubes:
[tex]\[27m^3 = (3m)^3\][/tex]
[tex]\[64n^3 = (4n)^3\][/tex]
So, we can rewrite the expression like this:
[tex]\[(3m)^3 + (4n)^3\][/tex]
Now, we can apply the sum of cubes formula with \(a = 3m\) and \(b = 4n\):
[tex]\[(3m)^3 + (4n)^3 = (3m + 4n)((3m)^2 - (3m)(4n) + (4n)^2)\][/tex]
We need to perform the operations inside the parentheses to get the final factors:
1. \((3m)^2 = 9m^2\)
2. \((3m)(4n) = 12mn\)
3. \((4n)^2 = 16n^2\)
Putting these together, we have:
[tex]\[(3m)^3 + (4n)^3 = (3m + 4n)(9m^2 - 12mn + 16n^2)\][/tex]
So, the factored form of the expression \(27m^3 + 64n^3\) is:
[tex]\[(3m + 4n)(9m^2 - 12mn + 16n^2)\][/tex]
Therefore, the factors of \(27m^3 + 64n^3\) are:
[tex]\[ (3m + 4n) \quad \text{and} \quad (9m^2 - 12mn + 16n^2) \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.